Simultaneous identification and analysis of cassane diterpenoids in Caesalpinia minax Hance by high‐performance liquid chromatography with quadrupole time‐of‐flight mass spectrometry. Issue 23 (27th October 2015) - Wu, Shilong; Wu, Zhaohua; Fu, Chaofan; Wu, Caiyue; Yuan, Jiuzhi; Xian, Xiaoyan; Gao, Huiyuan
Abstract : Cassane diterpenoids were successfully and simultaneously identified in Caesalpinia minax Hance by high‐performance liquid chromatography coupled with quadrupole time‐of‐flight tandem mass spectrometry. A total of 59 peaks were detected, and among them 51 compounds, including 41 furanocassane diterpenoids, 10 furanolactone cassane diterpenoids were simultaneously identified and characterized on the basis of the protonated molecule, retention behavior, and fragments in MS 2 . Ten compounds, including seven novel compounds, were identified or tentatively identified for the first time in C. minax . In a positive ion mode, the fragmentation pathways of cassane diterpenoids were also analyzed for the first time. The relative amounts of the five main diterpenoids (caesalpinin L, caesalpinin F2, bondcellpin C, caesalpinin E, and ξ‐caesalmin) were simultaneously quantified by high‐performance liquid chromatography. Results showed that the newly discovered and known components of C. minax can be used to determine the material basis of bioactivity; this method can also be applied to analyze cassane diterpenoids in herbal medicines from the genus Caesalpinia belonging to the family Fabaceae.